Solve (2x+3)(4x-2)=0

To solve a simulatious equation, you should place the contents of each bracket equal to 0.
so (2x+3)=0 and (4x-2)=0
Lets start with the equation on the left.
2x+3=0
Minus 3 from both sides of the equation leaving you with 2x=-3 Then divide both sides by 2 leaving the equation at x= -3/2 - this is your answer

for the equation on the right (4x-2)=0
4x-2=0
add 2 to both sides (as adding is opposite to minusing) giving you 4x=2 divide both sides by 4 leaving you with the answer x=2/4
(Note: This answer can be further simplified by dividing both the top and the bottom of the fraction by the same number - in this case both the top and the bottom can be divided by 2, leaving the alternate answer as 1/2)

Answered by Catherine P. Maths tutor

3571 Views

See similar Maths GCSE tutors

Related Maths GCSE answers

All answers ▸

If a cookie recipe requires 280g of flour for 12 cookies how much flour is needed to make only 9 cookies


x = 0.045 (45 recurring). Prove algebraically that x can be written as 1/22


You are given a sequence of numbers: -2, 12, 32, 58, 90, ... Work out the 7th term in this sequence.


y=6x+2 Find the gradient of the line and the y intersect


We're here to help

contact us iconContact usWhatsapp logoMessage us on Whatsapptelephone icon+44 (0) 203 773 6020
Facebook logoInstagram logoLinkedIn logo
Cookie Preferences